Safety and efficacy of plasma transfusion from exercise-trained donors in patients with early Alzheimer's disease: protocol for the ExPlas study. Issue 9 (6th September 2022) - Tari, Atefe R; Berg, Helene Haugen; Videm, Vibeke; Bråthen, Geir; White, Linda R; Røsbjørgen, Ragnhild Nyhus; Scheffler, Katja; Dalen, Havard; Holte, Espen; Haberg, Asta K; Selbaek, Geir; Lydersen, Stian; et al.
Abstract : Introduction: Given that exercise training reduces the risk of developing Alzheimer's disease (AD), induces changes in the blood composition and has widespread systemic benefits, it is reasonable to hypothesise that exercised plasma (ExPlas) may have rejuvenative properties. The main objective is to test safety and tolerability of transfusing ExPlas from young, healthy, fit adults to patients with mild cognitive impairment (MCI) or early AD. The study is a pilot for a future efficacy study. The key secondary objectives are examining the effect of plasma transfusions on cognitive function, fitness level, vascular risk profile, assessment of cerebral blood flow and hippocampal volume, quality of life, functional connectivity assessed by resting state functional MRI and biomarkers in blood and cerebrospinal fluid. Methods and analysis: ExPlas is a double-blinded, randomised controlled clinical single-centre trial. Patients up to 75 years of age with diagnosis early symptomatic phase AD will be recruited from two Norwegian hospitals. ExPlas is plasma drawn by plasmapheresis once a month for 4 months, from a total of 30 fit male donors (aged 18–40, BMI≤27 kg/m 2 and maximal oxygen uptake>55 mL/kg/min). All units will be virus inactivated by the Intercept method in accordance with procedures at St. Olavs University Hospital. Comparison with isotonic saline allows differentiation from a non-blood product. The main study consists of 6 rounds of examinations in addition to 12 plasma transfusions divided over three 4-week periods during study year-1. It is also planned to conduct follow-up examinations 2 and 5 years after baseline Ethics and dissemination: Written informed consent will be obtained from all participants and participation is voluntary. All participants have a next of kin who will follow them throughout the study to represent the patient's interest. The study is approved by the Regional Committee for Medical and Health Research Ethics (REK 2018/702) and the Norwegian Medicines Agency (EudraCT No. 2018-000148-24). The study will be published in an open access journal and results will be presented at numerous national and international meetings as well as on social media platforms. Trial registration number: EudraCT No. 2018-000148-24. ClinicalTrials.gov, NCT05068830